New Wine? New Wineskins? Values-based Reflections on the Changing Face of Healthcare Chaplaincy. (5th March 2015) - Paterson, Michael
Abstract : In the first of this series of three articles in Health & Social Care Chaplaincy, the author employed Ricoeur's typology – orientation, disorientation, reorientation – to explore Scottish healthcare chaplains' responses to the refocusing of spiritual care from a series of crisis-based hospital interventions to the promotion of wellbeing and resilience in local communities. In this second article the author treats this paradigm shift with a hermeneutic of suspicion and explores inherent issues of need, ability, value and power.